A Survey on Methods of Automatic Protocol Reverse Engineering - XiangDong Li; Li Chen (2011 Seventh International Conference on Computational Intelligence and Security, 2011)
Protocol reverse engineering is necessary for many security applications, and has been an important and active research topic. This paper makes a survey on automatic protocol reverse engineering, especially on the goals, methods, tools and their achievements. The targets and obstacles in automatic protocol reverse engineering are identified. Then the evolution of the technique and tools proposed for protocol reverse engineering are reviewed chronologically. Finally we summarize those difficulties and problems that are still open to solve, and envision the prospects of this field.